2017
DOI: 10.1080/15283488.2017.1379907
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits and Challenges of a Multiethnic-Racial Identity: Insight From Adults With Mixed Heritage

Abstract: The purpose of this inquiry was to explore the lived experiences of multiethnic-racial individuals (i.e., individuals with parents from different ethnic-racial groups). In-depth interviews were conducted with 29 adults from the United States with mixed ethnic-racial backgrounds ranging in age from 18 to 52 (female n = 20, male n = 9). We identified a number of themes related to perceived benefits (e.g., pluralistic world views, stronger sense of self) and challenges (e.g., identity tensions, communal concerns)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Self-enhancement is a value most akin to individualism (Schwartz, 2012) which has been associated with more often talking about autobiographical memories (Wang & Conway, 2004). Mixed individuals in the current study did not have higher self-enhancement values, but they may have a stronger sense of self because of their continuous need to legitimize their ethnic identity (Soliz, Cronan, Bergquist, Nuru, & Rittenour, 2017). This stronger sense of self may manifest in more often talking about their autobiographical memories when their values are oriented towards enhancement of the self.…”
Section: Discussionmentioning
confidence: 77%
“…Self-enhancement is a value most akin to individualism (Schwartz, 2012) which has been associated with more often talking about autobiographical memories (Wang & Conway, 2004). Mixed individuals in the current study did not have higher self-enhancement values, but they may have a stronger sense of self because of their continuous need to legitimize their ethnic identity (Soliz, Cronan, Bergquist, Nuru, & Rittenour, 2017). This stronger sense of self may manifest in more often talking about their autobiographical memories when their values are oriented towards enhancement of the self.…”
Section: Discussionmentioning
confidence: 77%
“…Although biracial Latinx-White people are known to experience unique forms of discrimination and challenges to their ethnic and/or racial identity integration(Jackson et al, 2012;Soliz et al, 2017), t-tests showed no mean differences between monoethnic Latinx and biracial Latinx-White people among measures of sexual and ethnic discrimination, identity integration, and salivary cortisol indices (all ps > 0.05). Given the small number of biracial Latinx-White people in this study, in an effort to yield more precise estimates, participants' monoethnic and biracial identities were included as a covariate in the main analyses.…”
mentioning
confidence: 85%
“…In ethnically mixed families, it is important which of the husband and wife belongs to the ethnic majority, so that in such families, the powers of the husband and wife in determining the language of communication within the family, choosing the language of education of the children, and choosing the names of the children are not the same, and in such matters, the party belonging to the ethnic majority decides mainly (Kutyavina, & Malysheva, 2010). However, in the scientific literature, there are also those who state that the existence of ethnically mixed families is a very important process in terms of bringing the cultures of different peoples and nations closer to each other and valuing each other (Soliz, Cronan, Bergquist, Nuru, & Rittenour, 2017). As mentioned by Merton (1941), the large number of inter-ethnic marriages reduces the probability of violent conflicts between these social groups.…”
Section: Literature Reviewmentioning
confidence: 99%